PENGARUH PELAYANAN AKADEMIK TERHADAP KEPUASAN MAHASISWA DI UNIVERSITAS ADVENT INDONESIA, BANDUNG - Silitonga, Rose (Jurnal Ekonomis, 2011)
Academic service conditions at the Universitas Advent Indonesia, Bandung today are felt not quite meet the expectations. This can be felt from the onset of complaints from both the internal and external, issues relating to academic services provided in terms of a mismatch between expectations and demands. On the other hand, is characterized by a reduced number of students over the past few years. The purpose of this study were: 1) To determine the effect of quality of service provided by Universitas Advent Indonesia received by students; 2) To determine the relationship of service that may affect student satisfaction Universitas Advent Indonesia; 3) To know how big the influence of academic services to the level of satisfaction of Universitas Advent Indonesia students. The method used in this research is descriptive methods. The population used as an object of research is Universitas Advent Indonesia students, Bandung 2010-2011 school year as many as 1429 people. Sampling technique used in this study is proportional stratified random sampling technique. From the calculation results obtained sample number as many as 94 students. The conclusion from the results of this study is that there is significant relationship between academic services tangible dimension, reliability, responsiveness, assurance and empathy to the satisfaction of Universitas Advent Indonesia students. Keywords: Tangible dimensions of service quality, reliability, responsiveness, assurance and empathy, Students Satisfaction.